The impact of derivatives on spot markets: Evidence from the introduction of bitcoin futures contracts - Patrick Augustin; Alexey Rubtsov; Donghwa Shin (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2022)
Cryptocurrencies provide a unique opportunity to identify how derivatives impact spot markets. They are fully fungible, trade across multiple spot exchanges at different prices, and futures contracts were selectively introduced on bitcoin (BTC) exchange rates against the USD in December 2017. Following the futures introduction, we find a significantly greater increase in cross-exchange price synchronicity for BTC-USD relative to other exchange rate pairs, as demonstrated by an increase in price correlations and a reduction in arbitrage opportunities and volatility. We also find support for an increase in price efficiency, market quality, and liquidity. The evidence suggests that futures contracts allowed investors to circumvent trading frictions associated with short sale constraints, arbitrage risk associated with block confirmation time, and market segmentation. Overall, our analysis supports the view that the introduction of BTC-USD futures was beneficial to the bitcoin spot market by making the underlying prices more informative.
Keywords: G12; G13; G14; O33; Y80; 330; bitcoin; blockchain; cryptocurrencies; derivatives; fintech; regulation